Wykorzystanie funduszy strukturalnych sposobem na poprawę konkurencyjności przedsiębiorstw sektora mleczarskiego w Polsce - Romaniuk, Krystyna (The Use of Structural Funds to Improve the Competitiveness of Enterprises of Dairy Sector in Poland, 2006)
The study was conducted at 29 Polish dairy cooperatives. The aim of the study is to find answer to the following questions: What was the quota that the dairy cooperatives applied for? What were the objectives and scope of the projects financed from the EU structural funds? What were the deadlines for the project implementation? The research method employed in the study was a survey. The total amount of project funding was PLN 83 018 250. In the majority of cases the structural funds were allocated for technology modernization, production facilities, industrial buildings and warehouses. These factors are crucial for improving the competitiveness of dairy cooperatives in Poland, since in the past the lack of financing in this sector was a barrier to their development. This indicates that the enterprises have adopted the right direction of changes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 279-284